Rancang Bangun Sistem Observasi Keadaan Atmosfer Bumi Menggunakan Drone - Lusiana Elmi Juwita; Suryadhi Suryadhi (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Observation of atmospheric data is an integral part of research activities in fields related to weather and climate. The technology that has developed today has measured environmental parameters vertically using atmospheric broadcasting technology, radio, a device that can be flown by atmospheric balloon vehicles that can measure vertical atmospheric parameters and transmit data via radio. Therefore, this study makes the atmosphere that is temperature, humidity, air pressure, wind and GPS. By using DHT11 sensor as temperature and humidity transducer, BMP280 sensor as an air pressure transducer, HMC5883l as a wind direction transducer, MQ135 as a Carbon Dioxide gas transducer, and GPS as the purpose of the sensor data will be stored and sent via 3DR radio telemetry.